Effect of plastic anisotropy on forming behavior of AA-6061 aluminum alloy sheet. (October 2016) - Barnwal, Vivek K; Tewari, Asim; Narasimhan, K; Mishra, Sushil K
AA-6061 (T6) aluminum alloy sheet is used extensively for structural applications in various automotive and aerospace industries due to its excellent mechanical and physical properties. Due to lower formability of this material in age-hardened (T6) condition, forming of complex-shaped components is a major challenge. Forming behavior of the sheet was studied in T6 condition using limit dome height tests by experiment and finite element method for three different sheet directions (rolling direction, inclined direction (ID) and transverse direction). Strain path diagrams were obtained from the experimental limit dome height tests and finite element method simulations from drawing to stretching region, and the results were compared for all the sheet directions. Forming limit diagrams were plotted using strain localization and fracture criteria from experimental and simulated strain path curves. Effect of plastic anisotropy on crack propagation direction was studied using finite element method, and it has been found that the direction of crack propagation was strongly dependent on plastic anisotropy ratio ("r" value) of the sheet in biaxial strain paths.